Fibrinolytic Proteins and Progression of Coronary Artery Disease in Relation to Gemfibrozil Therapy - Hamsten, Anders; Syvänne, Mikko; Silveira, Angela; Luong, Le-Anh; Nieminen, Markku S.; Humphries, Steve; Frick, M. Heikki; Taskinen, Marja-Riitta (Thrombosis and Haemostasis, 2000)
Impaired fibrinolytic function, mainly due to increased plasma plasminogen activator inhibitor-1 (PAI-1) activity, is common in patients with manifest coronary artery disease (CAD) and a predictor of recurrent cardiovascular events. We investigated the relationships of plasma tissue-type plasminogen activator (tPA) and PAI-1 antigen levels, plasma PAI-1 activity and PAI 4/5-guanosine (4G/5G) genotype to CAD progression in 203 middle-aged men participating in the Lopid Coronary Angiography Trial (LOCAT).A higher tPA antigen concentration, whether baseline or on-trial, was associated with a more severe global angiographic response (p < 0.05), an association mainly accounted for by progression of diffuse lesions in graft-affected segments (change in per-patient means of average diameters of segments haemodynamically related to bypass grafts). Plasma PAI-1 activity and mass concentration and 4G/5G PAI-1 genotype were unrelated to angiographic outcome measurements. tPA and PAI-1 antigen increased significantly in the gemfibrozil group (+11.3% and + 16.4%, respectively, p < 0.001), whereas there was no treatment effect on PAI-1 activity (median change 0.0%).It is concluded that fibrinolytic function does not substantially influence progression of CAD as assessed by angiography in middle-aged men. Furthermore, pronounced long-term lowering of serum triglycerides by gemfibrozil treatment does not significantly affect the plasma PAI-1 activity level but increases the plasma tPA and PAI-1 antigen concentrations.
Keywords: Atherosclerosis; thrombosis; gemfibrozil; coronary artery disease; angiography; fibrinolysis; lipoproteins